Ways to Prevent Calf Dyspepsia - Davlatov Karim Mamadmuso o’g’li; Saidov Abdurahmon Abduhalim o’g’li; Umirqulov Akbar Suvon o’g’li (Scientific Trends, 2024)
The article presents data on metabolic disorders in the body of cows excluded from milk as a consequence of etiological factors in calves dyspepsia and it’s prevention by adding sprouted verdure of the wheat, monocalcium phosphate and LPP-1 to the diet of cows.
Keywords: Hypotrophy, dyspepsia, diarrhea, hemoglobin, carotene, calcium, phosphorus, monocalciphosphate, LPP-1, trace elements, vitamins, prophylaxis, glucose, protein, leukocyte.